Mobile monitoring of air pollution − a position paper on use cases, good practices, challenges, and opportunities - Jules Kerckhoffs; Jelle Hofman; Jibran Khan; Matthew D. Adams; Magali N. Blanco; Priyanka deSouza; John L. Durant; Sasan Faridi; Scott Fruin; Steve Hankey; Mohammad Sadegh Hassanvand; Marianne Hatzopoulou; et al. (Environment International)
Mobile monitoring has proven to be a very efficient tool to measure and feed into models of air pollution as it complements fixed air quality monitoring networks by adding spatiotemporal resolution. This paper explores best practices, opportunities and challenges related to mobile monitoring of air pollutants, focusing on three key application areas, namely source-, exposure-, and health-related use cases. Use cases are linked to users, ensuring mobile monitoring is effectively tailored to diverse research and policy needs. Tailoring mobile monitoring involves experimental design choices (platform, instrumentation, route planning and spatiotemporal coverage) and data processing choices (data-only vs modelling) optimized towards the envisaged use case. This position paper aims to guide researchers and air pollution stakeholders in generating high-quality mobile monitoring datasets. We identify best practices, discuss monitoring strategies, and highlight future research directions. Additionally, mobile monitoring supports public engagement and actionability, allowing communities to advocate for cleaner air and drive behavior change.